Regulation of neurocoel morphogenesis by Pard6γb - Munson, Chantilly; Huisken, Jan; Bit-Avragim, Nana; Kuo, Taiyi; Dong, P. D.; Ober, Elke A.; Verkade, Heather; Abdelilah-Seyfried, Salim; Stainier, Didier Y.R. (Developmental Biology, 2008)
The Par3/Par6/aPKC protein complex plays a key role in the establishment and maintenance of apicobasal polarity, a cellular characteristic essential for tissue and organ morphogenesis, differentiation and homeostasis. During a forward genetic screen for liver and pancreas mutants, we identified a pard6γb mutant, representing the first known pard6 mutant in a vertebrate organism. pard6γb mutants exhibit defects in epithelial tissue development as well as multiple lumens in the neural tube. Analyses of the cells lining the neural tube cavity, or neurocoel, in wildtype and pard6γb mutant embryos show that lack of Pard6γb function leads to defects in mitotic spindle orientation during neurulation. We also found that the PB1 (aPKC-binding) and CRIB (Cdc-42-binding) domains and the KPLG amino acid sequence within the PDZ domain (Pals1-and Crumbs binding) are not required for Pard6γb localization but are essential for its function in neurocoel morphogenesis. Apical membranes are reduced, but not completely absent, in mutants lacking the zygotic, or both the maternal and zygotic, function of pard6γb, leading us to examine the localization and function of the three additional zebrafish Pard6 proteins. We found that Pard6α, but not Pard6β or Pard6γa, could partially rescue the pard6γbs441 mutant phenotypes. Altogether, these data indicate a previously unappreciated functional diversity and complexity within the vertebrate pard6 gene family. © 2008 Elsevier Inc. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Apicobasal polarity; Epithelium; Neurulation; Par6; Zebrafish